2014
DOI: 10.3892/mmr.2014.2966
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sevoflurane on leucine-rich repeat kinase�2-associated Drosophila model of Parkinson's disease

Abstract: Abstract.Patients with Parkinson's disease (PD) often require surgery, and therefore may receive inhalation anesthesia. However, it is currently unknown whether inhalation anesthetics affect the prognosis of the disease. Leucine-rich repeat kinase 2 (LRRK2) genetic mutations are the most common cause of familial PD, contributing to ~39% of all cases in certain populations. The aim of the present study was to determine the effects of inhaled anesthetics on PD, by observing the influence of sevoflurane on a LRRK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…We chose to use sevoflurane, one of the commonly used inhalational anesthetics, because it helps rapid induction and recovery. Shan et al [25] reported that sevoflurane aggravated the prognosis of PD in a Drosophila model. We attributed the lack of statistical significance in this study to the relatively short duration of DBS surgery and the follow-up due to short hospitalization period.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to use sevoflurane, one of the commonly used inhalational anesthetics, because it helps rapid induction and recovery. Shan et al [25] reported that sevoflurane aggravated the prognosis of PD in a Drosophila model. We attributed the lack of statistical significance in this study to the relatively short duration of DBS surgery and the follow-up due to short hospitalization period.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that TIVA has superior effects in inhibiting inflammatory responses to inhalational anesthetics [9,[17][18][19]. Shan et al [20] reported that the inhalational anesthetic sevoflurane has a negative effect and aggravates the prognosis of PD in a Drosophila model. We attributed the lack of statistical significance in this study to the relatively short duration of surgery and the follow-up of only 24 h after surgery may not have been sufficient to reveal cytokine changes.…”
Section: Discussionmentioning
confidence: 99%
“…Shan et al [20] reported that impairment of locomotor abilities is aggravated with exposure to sevoflurane in a Drosophila PD model. Tuon et al [12] reported that IL-17 levels decrease after physical training in an experimental mouse model of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Mason and colleagues showed that administration of sevoflurane changed the concentration of dopamine (DA) in the brain by impairing the transport synaptosomes of DA, thus leading to further damage of the dopaminergic system and locomotor dysfunction (Mason et al 1996). Additionally, sevoflurane severely aggravated the prognosis of PD in another causative gene LRRK2-associated Drosophila model by means of synaptic cholinergic deficits and impairment of locomotor abilities (Shan et al 2015). Interestingly, a recent study demonstrated that DJ-1 has the potential to protect neuronal cells against oxidative stress, mitochondrial dysfunction, and apoptosis induced by the inhaled anesthetic gas isoflurane (Liu et al 2015).…”
Section: Introductionmentioning
confidence: 99%